Enzootický potrat oviec v okrese Roznava - Sádecký, E; Trávnicek, M; Balascák, J; Brezina, R; Kazár, J; Urvölgyi, J; Flesár, I; Cizmár, J (Veterinarni medicina, 1978)
In the winter months of the year 1977, 64 dams out of 170 ewes pregnant for the first time miscarried on one farm in the locality G., Roznava district. Antibodies were revealed in 97% dams after the examination of the blood of 170 ewes from the abortion-affected flock; ornithosis antigen was employed for the examination in the complement-fixing reaction. In the cytoplasm of placentary cells of two miscarrying ewes chlamydiae were proved microscopically. The chlamydiae-strains designated LH-5109 and PK-5082 were isolated by inoculating placentary suspensions to the yolk sacs of chicken embryos. Both strains correspond to all the criteria necessitating the identification of chlamydiae (Storz, 1971). As miscarrying ewes in the course of abortions eliminate, with abortions and amniotic fluids, great amounts of chlamydiae to their environment, they represent a powerful source of infection to healthy animals housed on the same premises and to tending staff. Chlamydiae-antibodies were proved, by the complement-fixing reaction, in the blood of seven attendants out of all the eleven-member tending staff.
Keywords: Czechoslovakia; Abortion, Veterinary; infekce bakteriemi čeledi Chlamydiaceae; Československo; potrat u zvířat; ženské pohlaví; Sheep; zvířata; Pregnancy; Female; ovce; těhotenství; Chlamydiaceae Infections; Animals